The cinema at home: a means of communication and an effective tool for teaching - Meléndez Chávez, Sendy; Huerta González, Sara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The objective of this work was to know the experiences of the use of cinema as a means of communication and learning in nursing students of human sexuality. With a qualitative approach, with 19 participants, who manifested; learning new terms, generating changes in their academic, personal and family life, so that the cinema turned out to be not only an effective means of communication, but also a teaching strategy of a pedagogical, novel, acceptable, economic, interest and above all learning for young people during training from their homes in these times of pandemic.